Which patients do not seek additional medical care after a self-management class for low back pain? An observational cohort. (November 2019) - Garcia, Alessandra Narciso; Cook, Chad; Rhon, Daniel
Objectives: (1) To identify baseline variables associated with patients that sought no additional care during the 12 months following a single self-management education session for low back pain (LBP), and (2) in those who sought care, to determine whether the same variables were associated with low versus high downstream LBP-related healthcare utilization. Design: An observational cohort. Setting: Single large military hospital. Participants: A total of 733 patients with LBP. Intervention: Single self-management education session. Main outcomes: Eleven variables were explored in two distinct logistic regression models: (1) no additional care versus additional care, and (2) low versus high number of additional visits in the additional care group. Results: In the first model, not being on active duty service (odds ratio (OR) = 1.98, 95% confidence interval (CI) = 1.37–2.86), low baseline disability (OR = 1.02, 95% CI = 1.00–1.04), low baseline fear-avoidance related to work (OR = 1.02, 95% CI = 1.00–1.03), and, in the last year, no opioid prescriptions (OR = 1.44, 95% CI = 1.00–2.07), physical therapy (OR = 1.63, 95% CI = 1.00–2.65), or sleep disorder diagnosis (OR = 1.62, 95% CI = 1.05–2.51) significantly increased the odds that patients would not seek any additional care. In the second model, not being on active duty service (OR = 2.18, 95% CI = 1.38–3.46), low baseline disability (OR = 1.04, 95% CI = 1.02–1.06), and no opioid prescriptions in the prior year (OR = 2.19, 95% CI = 1.42–3.37) increased the odds that patients would have less visits (⩽2 visits). Conclusion: Our study found several variables that helped determine whether patients would seek little or no additional care during the 12 months following a self-management education class for LBP.